Modelling Collective Action in Public Health Crises: A Socio-Mathematical Approach - Dr Joydeb Patra; Dr Sthitadhi Das; Dr Prodipta Barman (The Bioscan, 2026)
Background and Aims: Vaccine reluctance, which is especially widespread in the context of the COVID-19 pandemic, is not only a psychological trait but also a complex socio-political process influenced by institutional trust, social connections, homophily, and normative pressure. This paper formulates vaccination acceptance as a group action process and constructs a rigorous socio- mathematical model to describe how individual attitudes interplay with those of groups during emergencies in the health sector.